Understanding Isaiah Berlin as Historian of Ideas: Lessons Learned for Muslim Scholars in Indonesia - Kamaruzzaman Bustamam-Ahmad (Ulumuna, 2021)
This article discusses the figure of Isaiah Berlin, a philosopher who studies the history of ideas in the West. Berlin has carried out the development of ideas in the West in his works. This article discusses the significance of ideas in the study of philosophy by looking at Berlin’s experience. It can be argued that the study model from Isaiah Berlin can be used as a model for studying ideas by Muslim scholars in Indonesia. In this country, Muslim scholars tend to neglect the study of ideas, significantly developed in the 1990s. Through a bibliographical study of the works of Isaiah Berlin, this article presents the intellectual foundations of Berlin in reconstructing philosophical concepts. It is argued that Muslim scholars in Indonesia should return to more studies of ideas or thoughts in society.